The Role of Microbiota in Drosophila melanogaster Aging - Arias-Rojas, Aranzazu; Iatsenko, Igor (Frontiers in Aging, 2022)
Intestinal microbial communities participate in essential aspects of host biology, including nutrient acquisition, development, immunity, and metabolism. During host aging, dramatic shifts occur in the composition, abundance, and function of the gut microbiota. Although such changes in the microbiota are conserved across species, most studies remain descriptive and at most suggest a correlation between age-related pathology and particular microbes. Therefore, the causal role of the microbiota in host aging has remained a challenging question, in part due to the complexity of the mammalian intestinal microbiota, most of which is not cultivable or genetically amenable. Here, we summarize recent studies in the fruit fly Drosophila melanogaster that have substantially progressed our understanding at the mechanistic level of how gut microbes can modulate host aging.